Efeitos do sotalol sobre o eletrocardiograma de alta resolução avaliados por ensaio duplo-cego cruzado randomizado - G. Maia, Ivan; Molina Costa, Angela; A. G. Alves, Paulo (JOURNAL OF CARDIAC ARRHYTHMIAS, 2020)
The effects of sotalol over the signal-averaged electrocardiogram were evaluated in a population with idiophatic ventricular arrhythmias by a randomized double-blind crossover trial. No modilication in the analysed paramethers (root mean square, low amplitude signals, ORS duration) were observed in drugresponsive patients, while in the group where the drug was not effective, a signilicant rise on the low amplitude signals was detected with a mean increment 01 11.2 ± 4.8 ms.